DIRECTIONS AND RESERVES OF POST-WAR RECONSTRUCTION ECONOMY OF UKRAINE - Kaziuka , N. P.; Sheketa , Ye. Yu. (The actual problems of regional economy development, 2022)
In the article, the authors attempted to assess the socio-economic consequences of Russia's full-scale aggression on the territory of Ukraine. The main problems faced by our economy are identified, in particular: the outflow of foreign and domestic capital from the country; destruction of logistics infrastructure; several million refugees who were forced to emigrate to other countries or to other regions within the country and lost their jobs - the main source of income, they fell out of the economic cycle of the country because such citizens are unable to consume and produce products and services, pay taxes, etc .; inflation, falling purchasing power of the national currency, the need for state funding of social benefits for the population and funding of the Armed Forces of Ukraine, which provokes an increase in the state budget deficit, which due to the war is replenished at a much slower pace. The forecast phenomena that our country's economy will face due to Russian aggression and large-scale destruction are described. It is determined that the analogue of the “Marshall Plan”, which contributed to the almost complete recovery of European economies in the post-World War II era, can become a basic starting point for the rapid recovery of our state. This comprehensive plan should provide for the restoration of the destroyed economy, modernization of state structures and the maximum acceleration of Ukraine's development. The main factual and forecast indicators for estimating the level of losses of the national economy due to hostilities on the territory of Ukraine are analyzed. The main stages are highlighted for successful economic transformation in our country. In particular: development and implementation of a modern innovative concept of economic transformation taking into account the real geopolitical situation; implementation of the strategy developed and agreed by domestic scientists, researchers, scientists and the government for the restoration and development of territories that were under occupation or were damaged by rocket fire; identification of priority sectors of the economy.